Общий метод решения некоторых задач по стабилизации и дестабилизации движения - Барьяхтар, В.Г.; Самар, А.В. (Інститут математики НАН України, 2007)
Продемонстровано повну математичну аналогію в описі руху електрона в періодичному полі та явища параметричного резонансу (ПР). Сформульовано зонний підхід до аналізу явища ПР. Для осцилятора під дією зовнішньої сили, що описується функцією Вейєрштрасса, обчислено інкременти наростання коливань і сформульовано умову ПР. Для відомої задачі про маятник із вібруючою точкою підвісу за допомогою рівняння Ламе знайдено точні умови стабілізації маятника у верхньому (нестійкому) положенні рівноваги. We demonstrate the complete mathematical analogy between the description of motion of an electron in periodic field and the phenomenon of resonance. We formulate a zone approach to the analysis of the phenomenon of parametric resonance. For an oscillator under action of external force described by the Weierstrass function, we compute increments of oscillation increase and formulate the condition of parametric resonance. For the known problem of a pendulum with vibrating point of suspension, by using the Lamé equation, we find exact conditions of the stabilization of pendulum in the upper (unstable) equilibrium position.